Human development report 2000 (United Nations Development Programme, 2000)
This work provides an analysis of two interrelated and intertwined issues. Human rights and human development are mutually reinforcing and culminate in enlarged human freedom. The report traces the history of the struggle for human rights and outlines the rights agenda for the 21st century.